2002
DOI: 10.1016/s1386-9477(01)00432-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a quantum Hall insulator in an InGaAs/InP heterostructure

Abstract: We study the quantum critical behavior of the plateau-insulator (PI) transition in a low mobility In0.53Ga0.47As/InP heterostructure. By reversing the direction of the magnetic field (B) we find an averaged Hall resistance ρxy which remains quantized at the plateau value h/e 2 throughout the PI transition. We extract a critical exponent κ ′ = 0.57 ± 0.02 for the PI transition which is slightly different from (and possibly more accurate than) the established value 0.42 ± 0.04 as previously obtained from the pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
5
16
0
Order By: Relevance
“…This is also true if we use a much smaller value of , e.g., = 0.42 previously reported for the PP transitions of these InGaAs/ InP heterostructures. 22,24 We stress that our magnetotransport experiments carried out on different samples [18][19][20]15,27,28 provide solid evidence for an intrinsic critical exponent = 0.58 for the PI transition. The critical exponent is obtained directly from the xx Ϸ 0 ͑͒ data.…”
Section: Discussion and Summarymentioning
confidence: 64%
See 2 more Smart Citations
“…This is also true if we use a much smaller value of , e.g., = 0.42 previously reported for the PP transitions of these InGaAs/ InP heterostructures. 22,24 We stress that our magnetotransport experiments carried out on different samples [18][19][20]15,27,28 provide solid evidence for an intrinsic critical exponent = 0.58 for the PI transition. The critical exponent is obtained directly from the xx Ϸ 0 ͑͒ data.…”
Section: Discussion and Summarymentioning
confidence: 64%
“…It was prepared in the form of a Hall bar with a channel width W of 650 m and length L between the voltage contacts of ϳ1100 m. Previous magnetotransport experiments carried out on the same sample confirmed scaling in the quantum Hall regime. 15,18,19,24 Reference 24 focused on the PP transitions =4→ 3, 3 → 2, and 2 → 1, for which it was demonstrated that the components of the resistivity tensor obey scaling, i.e., the maximum slope in the Hall resistivity ͑d xy / dB͒ max and the inverse of the half width of xx between adjacent quantum Hall plateaus ͑⌬B͒ −1 both diverge algebraically with temperature as T − with a critical exponent = 0.42. 22 In Ref.…”
Section: Sample Choice and Magnetotransport Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we briefly address the principles of scaling and delineate our methodology to disentangle the quantum critical aspects of the two-dimensional electron gas from the sample dependent effects. Next we review the results of recent high-field magnetotransport studies carried out on different InGaAs/InP heterostructures (HS) [1,6,8,10] and an InGaAs/GaAs quantum well (QW) [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…the electron energy [2]. Similarly, it is now conclusively established that plateau-plateau and insulator-plateau transitions exhibit the same critical behavior [3][4][5][6].However, the value of the Hall resistance R H in this insulating phase (at large magnetic field) is still rather controversial. Various experiments have found that R H remains very close to its quantized value h/e 2 even deep in the insulating regime [4-6] with longitudinal resistance R L > h/e 2 .…”
mentioning
confidence: 99%